2022
DOI: 10.4018/joeuc.308814
|View full text |Cite
|
Sign up to set email alerts
|

Smart Health

Abstract: In recent decades, healthcare organizations around the world have increasingly appreciated the value of information technologies for a variety of applications. Three of the new technological advancements that are impacting smart health are metaverse, artificial intelligence (AI), and data science. The metaverse is the intersection of three major technologies — AI, augmented reality (AR), and virtual reality (VR). Metaverse provides new possibilities and potential that are still emerging. The increased work eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The structure was quickly divided by extracting the heading information in the documents. Because it is an undirected graph structure, the CRF method avoids the dependence of the HMM method on state transfer in the Markov chain (Nuka et al 2022), and therefore, the CRF method has wide application in text subdivision and structure delineation (Yang et al 2022). Thus, in this paper we completed the text delineation by this method, and the results showed that the CRF method has obvious advantages.…”
Section: Discussionmentioning
confidence: 87%
“…The structure was quickly divided by extracting the heading information in the documents. Because it is an undirected graph structure, the CRF method avoids the dependence of the HMM method on state transfer in the Markov chain (Nuka et al 2022), and therefore, the CRF method has wide application in text subdivision and structure delineation (Yang et al 2022). Thus, in this paper we completed the text delineation by this method, and the results showed that the CRF method has obvious advantages.…”
Section: Discussionmentioning
confidence: 87%
“…First, big data and data science techniques can be used to provide valuable reference data for university management decisions by measuring, recording, storing, counting, and analyzing data on a large scale and over time. With a large amount of data, prediction, clustering, and relationshipmining techniques can be used (Yang et al, 2022). Prediction technology allows administrators to better evaluate the possibility of various outcomes, such as enrolment and placement trends, and the development and growth of various disciplines.…”
Section: Discussion and Research Contributionsmentioning
confidence: 99%
“…As virtual reality and augmented reality (VR/AR), technologies continue to enhance there will be disruptive changes, especially for medical surveillance (Yang et al, 2022). Expanded Reality Healthcare Transformation is a holographic delivery, mixed reality platform that brings digital connections to life and provides new ways to teach, learn, and virtually perform tasks remotely (Catalano et al, 2022;Steike et al, 2022;Wang, Ning, Li et al, 2022).…”
Section: Metaverse X Medicalmentioning
confidence: 99%